2004
DOI: 10.1056/nejmoa041406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reducing Interns' Work Hours on Serious Medical Errors in Intensive Care Units

Abstract: Interns made substantially more serious medical errors when they worked frequent shifts of 24 hours or more than when they worked shorter shifts. Eliminating extended work shifts and reducing the number of hours interns work per week can reduce serious medical errors in the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
958
3
36

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,554 publications
(1,027 citation statements)
references
References 41 publications
30
958
3
36
Order By: Relevance
“…Several studies have been conducted to determine the relationship between work and sleep hours and rates of medical errors among physicians. These studies have concluded that elimination of extended shifts decreased attentional failures during night duty [3,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to determine the relationship between work and sleep hours and rates of medical errors among physicians. These studies have concluded that elimination of extended shifts decreased attentional failures during night duty [3,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Even after these modifications, concerns remained about how compliant residents were with the duty hour rules, 2 and one rigorous study suggested that further reductions in maximum shift length could lead to safer patient care. 3 The Institute of Medicine (IOM) conducted an investigation in 2008 and published recommendations for further reductions in resident duty hours. 4 Partially in response to the IOM report, the ACGME convened a duty hours task force to examine the issues and propose revisions in the duty hour standards.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, sleep deprivation impairs residents' clinical performance. Shorter shifts have been associated with fewer medical errors in five out of five studies 8,44,45 . On the other hand, patient handovers generally increase as duty-hours decline and the risk of PAEs is five-fold higher when interns are cross-covering 46 .…”
Section: Discussionmentioning
confidence: 89%